2023
DOI: 10.1038/s41419-023-05634-1
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis and degenerative diseases of the elderly

Abstract: Pyroptosis is a recently described mechanism of programmed cell death mediated by proteins of the gasdermin family. Widely recognized signaling cascades include the classical, non-classical, caspase-3-dependent gasdermin E and caspase-8-dependent gasdermin D pathways. Additional pyroptotic pathways have been subsequently reported. With the rising prevalence of advanced age, the role of pyroptosis in the degenerative diseases of the elderly has attracted increased research attention. This article reviews the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Another key factor leading to maladaptive brain plasticity is neuroinflammation, which can reduce neurogenesis and alter synaptic reorganization (Afridi & Suk, 2023; Maggio et al, 2013; Singhal & Baune, 2017; Tang et al, 2016). UCMS mice exhibited signs of neuroinflammation, evidenced by increased density of IBA1+ cells in the DG of the hippocampus and increased protein levels of cleaved caspase‐1, which activates pro‐inflammatory cytokines IL‐1 β and IL‐18 (Arend et al, 2008; Miao et al, 2011; Zhou et al, 2023). Increased hippocampal protein levels of mCSF, a secreted growth factor that regulates the proliferation and survival of microglial cells (Imai & Kohsaka, 2002; Pons & Rivest, 2018; Smith et al, 2013), might contribute to the observed increase in microglial cell density in the DG of UCMS mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key factor leading to maladaptive brain plasticity is neuroinflammation, which can reduce neurogenesis and alter synaptic reorganization (Afridi & Suk, 2023; Maggio et al, 2013; Singhal & Baune, 2017; Tang et al, 2016). UCMS mice exhibited signs of neuroinflammation, evidenced by increased density of IBA1+ cells in the DG of the hippocampus and increased protein levels of cleaved caspase‐1, which activates pro‐inflammatory cytokines IL‐1 β and IL‐18 (Arend et al, 2008; Miao et al, 2011; Zhou et al, 2023). Increased hippocampal protein levels of mCSF, a secreted growth factor that regulates the proliferation and survival of microglial cells (Imai & Kohsaka, 2002; Pons & Rivest, 2018; Smith et al, 2013), might contribute to the observed increase in microglial cell density in the DG of UCMS mice.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that an inflammatory form of cell death, termed pyroptosis contributes to decreased microglial cell density in VDD mice, as cleaved caspase‐1 protein levels were increased in the DG of VDD mice. Cleavage of pro‐caspase‐1 results in pyroptosis and the release of highly pro‐inflammatory cytokines IL‐1 β and IL‐18 (Miao et al, 2011; Zhou et al, 2023). In addition to the detrimental effects of pro‐inflammatory cytokine release during inflammasome activation, microglial cell depletion in VDD conditions could also impair physiologically relevant functions of microglia, such as providing trophic support to neurons via secretion of IGF‐1 and transforming growth factor β , phagocytosis and removal of apoptotic neurons (Amanollahi et al, 2023; Wohleb et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LPS, which originates from bacterial cell walls, has been found to induce non-classical pyroptosis models [ 25 ]. Given that IVDD primarily occurs under aseptic conditions and is associated with classical pathway-related pyroptosis [ 26 ], we excluded LPS. As potent oxidizing agents, peroxides can directly react with our TMP NPs, which have robust reducing properties [ 27 ], thereby potentially affecting the modeling process, which may obscure the direct effects of the NPs on pyroptosis.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, GSDMD is a direct target of inflammatory caspases (caspase-1, 4, 5, and 11). In molecular terms, GSDMD-mediated pyroptosis can be classified into two distinct pathways: classical and non-classical pyroptotic pathways [ 60 ]. The classical pyroptotic pathway involves the recognition of DAMPs and PAMPs by Toll-like receptors (TLRs) and Nod-like receptors (NLRs) in response to intracellular and extracellular stimulation [ 61 ].…”
Section: The Crosstalk Between Caspase-1 4 5 11/gsdmd-mediated Pyropt...mentioning
confidence: 99%